2023
DOI: 10.1097/md.0000000000035813
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of cognitive impairments on treatment compliance and quality of life in patients with Continuous Ambulatory Peritoneal Dialysis (CAPD)

Caixia Wu,
Ran Yu,
Qingju Li
et al.

Abstract: The aim of this study is to investigate the impact of cognitive impairments on treatment compliance and quality of life in patients with Continuous Ambulatory Peritoneal Dialysis (CAPD). A cross-sectional study was conducted among patients with CAPD at the Department of Nephrology, Lianshui People’s Hospital from October 2021 to May 2022. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA), and the End-Stage Renal Disease Adherence Questionnaire was used to evaluate treatment complia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…In this regard, several lines of evidence point out that Klotho may be relevant for normal cognition. In the absence of CKD, the serum levels of Klotho have shown significant associations with the scores in tests intended to evaluate different cognition domains, such as the Mini-Mental State Examination, the Clinical Dementia Rating, or the Digit Symbol Substitution test [23,24], while low concentrations of Klotho have been related to worse cognition [10]. In line with these observations, Klotho overexpression has been evidenced to improve cognitive function in nonhuman primates [25].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In this regard, several lines of evidence point out that Klotho may be relevant for normal cognition. In the absence of CKD, the serum levels of Klotho have shown significant associations with the scores in tests intended to evaluate different cognition domains, such as the Mini-Mental State Examination, the Clinical Dementia Rating, or the Digit Symbol Substitution test [23,24], while low concentrations of Klotho have been related to worse cognition [10]. In line with these observations, Klotho overexpression has been evidenced to improve cognitive function in nonhuman primates [25].…”
Section: Discussionmentioning
confidence: 78%
“…Thus, it is not surprising that at least part of the relevance of CKD-associated cognitive dysfunction relies on lower treatment compliance [43] along with the worse quality of life experienced by these patients. In this sense, very recent studies have reported apathy symptoms in patients with CKD and lower scores in terms of physical function, social and emotional function, and mental health, among other parameters [24,44].…”
Section: Discussionmentioning
confidence: 94%